Journey to becoming a culturally responsive science educator: reflections about use and barriers from graduate teaching assistants at a Minority-Serving Institution - McAnally, Kaylyn; Barron, Hillary A.; Woodruff, Isabella; Beaster-Jones, Laura; Menke, Erik; Kranzfelder, Petra (Frontiers in Education, 2024)
IntroductionA pedagogical framework with the aim of dismantling sociostructural disparity and systemic oppression is culturally responsive science teaching (CRST). Although CRST has been linked with improved student empowerment, self-efficacy, and ethnic and academic identity, more research is needed to assess whether graduate teaching assistants (TAs) in college science are familiar with and prepared to engage in CRST. We conducted two training sessions for inclusive teaching practices and CRST during a graduate TA teaching professional development course at a research-intensive Minority-Serving Institution (MSI).MethodsWe collected surveys, written reflections, and session artifacts from five graduate TAs participants and used qualitative methods to generate an understanding of their experiences with inclusive teaching and CRST.ResultsResults from this exploratory study indicated that graduate TAs felt they lacked training in inclusive practices and CRST, but still were intentional in providing their students with individualized attention and tried to make sociopolitical connections in their teaching. Also, they reported using inclusive practices and CRST by encouraging shared student experiences and promoting growth mindsets. A lack of time and training remained a barrier to implementation.DiscussionThese findings can inform future inclusive teaching professional development, which aims to bolster instructor's inclusive and culturally responsive science teaching practices, especially at MSIs.